Local leaders and the environment: little resilience and influence to produce a sustainable environment - Cordeiro, Gustavo Simões (2021)
The Legal Amazon region (LAR) consists on a complex area where multiple actors coexist with conflicting interests. Indigenous population, agribusiness entrepreneurs and small producers are examples of individuals with different behaviors concerning the economic development and deforestation of the area. In this sense, research has been conducted in order to evaluate the impacts of agricultural development and the rise of deforestation levels, the influence of economic incentives on economic development and deforestation and the impact of institutional incentives on deforestation reduction. However, the role of local leadership on these matters has not been analyzed so far. An efficient local leader would be the one who is resilient (e.g. promote both economic development and deforestation reduction on his municipality). Therefore, in our study we test if local leaders are resilient in the Legal Amazon environment, whether or not they make use of economic and/or institutional incentive to promote economic development and deforestation reduction and whether or not sustainable top leaders (e.g. state governors) influence the actions of local leaders (e.g. mayors). For this, we use a Regression Discontinuity methodology and a quasirandomized experiment (elections with a margin of victory close to zero). Our sample comes from multiple databases and includes over 18000 observations from 755 LAR distinct municipalities for the period between 1996 and 2016. Amongst our results, we identify that local farmer leaders promote economic development but do not produce significant changes on deforestation levels. We also identify that economic incentives are used by these local leaders, but institutional incentives are not. Finally, we identify that top level leaders do not influence local leaders on their actions on behalf of being resilient.